1997
DOI: 10.1209/epl/i1997-00406-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface roughness on bulk-disorder–induced wetting

Abstract: PACS. 68.45Gd -Wetting. PACS. 05.70Fh -Phase transitions: general aspects. PACS. 82.65Dp -Thermodynamics of surfaces and interfaces.Abstract. -Transfer-matrix results in 2D show that wetting of a rough, self-affine wall induced by bulk bond disorder turns discontinuous as soon as the wall roughness exponent ζW exceeds ζ0 = 2/3, the spatial anisotropy index of interface fluctuations in the bulk. For ζW < 2/3 critical wetting is recovered, in the same universality class as for the flat-wall case. These and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…In summary, our RG picture demonstrates first-order wetting in 2D with sufficiently rough substrates exerting short range forces on the interface. This is consistent with earlier numerical work suggestive of discontinuous transitions [8,16]. The threshold for first-order wetting is precisely identified as ζ w = 1/2 in the case of ordered bulk.…”
Section: And the Overbar Indicatingsupporting
confidence: 91%
See 3 more Smart Citations
“…In summary, our RG picture demonstrates first-order wetting in 2D with sufficiently rough substrates exerting short range forces on the interface. This is consistent with earlier numerical work suggestive of discontinuous transitions [8,16]. The threshold for first-order wetting is precisely identified as ζ w = 1/2 in the case of ordered bulk.…”
Section: And the Overbar Indicatingsupporting
confidence: 91%
“…Numerical results in ref. [16] support this conclusion, giving evidence of first-order wetting for sufficiently large ζ w and finite disorder. Similar arguments apply to long range forces in SF and, for ζ w > ζ * , in MF regime.…”
Section: And the Overbar Indicatingsupporting
confidence: 55%
See 2 more Smart Citations
“…Recent studies of filling transitions for fluids in 3D wedges [1,2] have revealed the much stronger influence of interfacial fluctuations compared with wetting at flat and rough substrates [3][4][5][6][7]. Encouragingly effective Hamiltonian predictions for the critical exponents at continuous (critical) wedge filling with short-ranged forces have been confirmed in large scale Ising model simulation studies [8].…”
mentioning
confidence: 98%